2003
DOI: 10.1017/s0022112003004427
|View full text |Cite
|
Sign up to set email alerts
|

On the convectively unstable nature of optimal streaks in boundary layers

Abstract: International audienceThe objective of the study is to determine the absolute/convective nature of the secondary instability experienced by finite-amplitude streaks in the flat-plate boundary layer. A family of parallel streaky base flows is defined by extracting velocity profiles from direct numerical simulations of nonlinearly saturated optimal streaks. The computed impulse response of the streaky base flows is then determined as a function of streak amplitude and streamwise station. Both the temporal and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 46 publications
7
67
3
Order By: Relevance
“…The propagation speed does not appear to be sensitive to the profile and amplitude of streaks. Similar values were obtained from numerical studies of impulse propagation in a boundary boundary perturbed by an optimal disturbance (Brandt et al 2003;Schlatter et al 2008). The spatial growth rates of unstable modes, calculated by solving the spatial eigenvalue problem as described above, are displayed in figure 13c.…”
Section: Streak Instabilitysupporting
confidence: 56%
See 1 more Smart Citation
“…The propagation speed does not appear to be sensitive to the profile and amplitude of streaks. Similar values were obtained from numerical studies of impulse propagation in a boundary boundary perturbed by an optimal disturbance (Brandt et al 2003;Schlatter et al 2008). The spatial growth rates of unstable modes, calculated by solving the spatial eigenvalue problem as described above, are displayed in figure 13c.…”
Section: Streak Instabilitysupporting
confidence: 56%
“…The sinuous mode instability was found to be more dangerous, and occurs when the streak amplitude, measured by its streamwise velocity, exceeds a threshold 0.26U ∞ . The instability has been shown to be of convective nature (Brandt et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It features at all times a pair of elongated low-speed streaks. These streaks support convective instabilities in the form of timedependent wavy modulations [18]. Visualization of the vortices using the 2 vortex identification criterion [19] reveals longitudinal vortices staggered on the flanks of the streaks, as well as hairpin-shaped vortices forming precisely above the region where streaks pinch.…”
mentioning
confidence: 84%
“…4. The lowest velocity is the signature of the streaks near the wall, the others corresponding to convective streak instabilities [18]. Both depart clearly from the Blasius profile, the departure being maximal closest to the wall, as in the turbulent regime [25].…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 27 Januamentioning
confidence: 94%
“…Brandt et al (2003) found that the instability of optimal streaks is convective and that the streaks behave as amplifiers of external noise. The secondary instabilities and the associated modes can be calculated through linear Floquet analyses of the streak base flow extracted from DNS or experiential results (Elofsson, Kawakami & Alfredsson 1999;Ricco, Luo & Wu 2011).…”
Section: Secondary Instabilities Of Streaksmentioning
confidence: 99%